Современные женщины: по-прежнему «в тени» мужчин? - Сиденко, Д. А. (ХНУРЕ, 2019)
Women in modem society. Kazan has the historical background of the emergence of this topic. The main problems that a woman faces are identified. Conclusions were made about the current role of women in society